CEMARAN PESTISIDA KARBAMAT DALAM AIR DANAU BUYAN BULELENG BALI - Putra Manuaba, I. B. (Jurnal Kimia (Journal of Chemistry); Vol. 3, No. 1 Januari 2009)
Pesticide is a very important material for protecting plant, animal, and controlling vector-borne diseases. The use of pesticide by farmer at Lake Buyan area is inevitable. The aim of this study is to investigate carbamate pesticide residual contaminant in water of Lake Buyan. This is an observational study to investigate carbamate contaminant in water of Lake Buyan. Sample preparation for this purposed was carried out following the standard method. GC-MS was employed in order to determine the carbamate pesticide contaminant. Carbamate pesticide contamination, i.e. carbofurane and methomyl were observed on 55 water sampling point taken from 5 zone. The residual contaminant of carbofurane and methomyl were 6.1 and 8.9 ppb, respectively. Total residual contaminant was 15.0 ppb with, which was bellow the threshold concentration of 100 ppb (SK Gubernur Bali No. 515 Tahun 2000).
Keywords: carbamate pesticide, vector-borne disease, protecting plant, residu